Islamic Counseling Services In The Development Of Spiritual Intelligence In Integrated Islamic First High School Students Al-Washliyah 20 Medan - Saiful Akhyar Lubis; Abdurrahman Abdurrahman; Annisa Riftah Andreani (At-Tarbiyat, 2021)
This study aims to determine: 1) to analyze Islamic counseling services for students of SMP IT Alwashliyah 20 Medan. 2) Analyzing the spiritual Intelligence of students of SMP IT Alwashliyah 20 Medan. 3) Analyzing Islamic Counseling services in Fostering spiritual Intelligence of students of MP IT Alwashliyah 20 Medan. The method used is a qualitative method with triangulation techniques, and the main subject is the Counseling Guidance teacher. The results showed that: 1) The counseling service used in this study is an individual counseling service, where this service is very effective when providing guidance. 2) Spiritual intelligence at SMP IT Alwashliyah 20 Medan is excellent because in subjects and activities outside of class hours, there are many activities in religious matters that can further improve students 'spiritual intelligence 3) Counseling Services in fostering student's spiritual intelligence are very effective because spiritual intelligence is assessed Individually with individual counseling services students can feel more comfortable and calm in terms of consulting.